Technological innovations in pulse production - Mishra, B. (International Food Policy Research Institute, 2017)
Chapter 4 looks at the technology, with special importance given the stagnation in pulses’ yield as compared with that of other crops. Yield improvement in pulses will be needed to overcome the position of advantage that now favors cereals and oilseeds. To date, the history of technology improvements in pulses has been mixed, with the pace of development and adoption picking up only in the past decade or so. With muted supply response in pulses driven by technology and agricultural policies, India has faced a persistent deficit in pulses that has led to significant imports.